MRI shows increased sciatic nerve cross sectional area in inherited and inflammatory neuropathies. Issue 11 (22nd October 2010) - Sinclair, C D J; Miranda, M A; Cowley, P; Morrow, J M; Davagnanam, I; Mehta, H; Hanna, M G; Koltzenburg, M; Reilly, M M; Yousry, T A; Thornton, J S
Abstract : Measurements of the cross sectional area of the sciatic nerve are described in a group of 10 patients with genetically confirmed Charcot–Marie–Tooth disease type 1A (CMT1A), nine patients with chronic inflammatory demyelinating polyneuropathy (CIDP) and 10 healthy controls using MRI. One mid-thigh of each individual was imaged using a short tau inversion recovery sequence and the nerve appearance evaluated radiologically with respect to the signal intensity and visibility of the internal neural structure. The cross sectional area of the sciatic nerve of each individual was measured by defining irregular enclosing regions of interest on the MRI images. The sciatic nerve area was enlarged in both CMT1A (p<0.001) and CIDP (p=0.008) compared with controls and in CMT1A compared with CIDP (p<0.001). Median (interquartile range) areas were 67.6 (16.2) mm 2 for the CIDP group, 135.9 (46.5) mm 2 for the CMT1A group and 43.3 (19.9) mm 2 for the control group. The critical upper value for discriminating pathologically enlarged nerves from normal controls with p<0.05 was 64.4 mm 2 . Quantification of sciatic nerve hypertrophy on MRI may be of assistance in cases where the diagnosis is still in doubt, providing an objective pathological marker complimenting other clinical investigations.